2016
DOI: 10.1371/journal.pone.0165614
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Community-Based TB/HIV Screening and Linkage to Care in Rural South Africa

Abstract: South Africa has one of the highest burdens of TB worldwide, driven by the country’s widespread prevalence of HIV, and further complicated by drug resistance. Active case finding within the community, particularly in rural areas where healthcare access is limited, can significantly improve diagnosis and treatment coverage in high-incidence settings. We evaluated the potential health and economic consequences of implementing community-based TB/HIV screening and linkage to care. Using a dynamic model of TB and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 51 publications
2
19
2
1
Order By: Relevance
“…This study indicates that TB screening among PL HIV is the most cost-effective strategy. The result consistent with past studies, which revealed TB screening among HIV is cost effective in both community and hospital settings (15,16). HIV is a well-known risk factor for TB infection in low-and middle-income countries (1).…”
Section: Discussionsupporting
confidence: 90%
“…This study indicates that TB screening among PL HIV is the most cost-effective strategy. The result consistent with past studies, which revealed TB screening among HIV is cost effective in both community and hospital settings (15,16). HIV is a well-known risk factor for TB infection in low-and middle-income countries (1).…”
Section: Discussionsupporting
confidence: 90%
“…Although modeling has confirmed the impact on reducing incidence and mortality from TB and HIV [ 30 ], these findings require confirmation in other regions. Furthermore, a recent study has demonstrated the cost effectiveness of the integrated TB/HIV CBICF strategy in rural resource-limited regions [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The intensified case finding was found to be the single most effective intervention for TB incidence, with around a 25% reduction over 10 years and a comparable impact on combined TB and HIV mortality as expanded ART policies. Gilbert et al [125] built on this to evaluate the projected cost-effectiveness of their intensified case finding strategy, finding it cost-effective in rural South Africa.…”
Section: Population-level Impact Of Interventionsmentioning
confidence: 99%